2022
DOI: 10.1108/bpmj-11-2021-0694
|View full text |Cite
|
Sign up to set email alerts
|

A hermeneutic research on project management approaches applied in a business process re-engineering project

Abstract: PurposeBusiness process re-engineering (BPR) initiatives are complex endeavours which require many factors to ensure success. However, most studies focus on the organisational processes and improvement within the organisation itself and less on the project team and management dynamics. The study aimed to identify factors that enabled the completion of a BPR, in a technical firm, based on reflections on the project management style.Design/methodology/approachThe study entailed a descriptive and interpretive cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 65 publications
(175 reference statements)
0
5
0
Order By: Relevance
“…In addition, adopting new technologies may not be well received by the intended users, a view supported by Okoro et al (2023). Consequently, attention to how employees perceive changes in the workplace and change management systems is critical as this may affect adoption, a view supported by Musonda and Okoro (2022) and Sim (2022). Intended or new users should embrace new learning opportunities to increase capabilities in their roles in the management of buildings and structures and ultimately improve productivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, adopting new technologies may not be well received by the intended users, a view supported by Okoro et al (2023). Consequently, attention to how employees perceive changes in the workplace and change management systems is critical as this may affect adoption, a view supported by Musonda and Okoro (2022) and Sim (2022). Intended or new users should embrace new learning opportunities to increase capabilities in their roles in the management of buildings and structures and ultimately improve productivity.…”
Section: Resultsmentioning
confidence: 99%
“…This will then require digital tools and monitoring of the work-life balance (De Bruyne and Gerritse, 2018). Other studies suggested sharing the risks involved to cushion the impact of the large investment, upskilling and training of FM professionals, appropriate relationship and change management structures (De Bruyne and Gerritse, 2018; Ullah and Sepasgozar, 2019; Musonda and Okoro, 2022). The relationship between management and employees also need to change to accommodate change management issues while implementing new technologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…BPR, being a multidisciplinary concept, may have gained traction due to its connections with various fields such as management, information technology, organizational behaviour and strategy. Today, BPR is performed with different elements and factors in various business fields (Al-Anqoudi et al, 2021;Srinivas et al, 2021;Lufti et al, 2022;Musonda and Okoro, 2022;Battilani et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Today, BPR is performed with different elements and factors in various business fields (Al-Anqoudi et al ., 2021; Srinivas et al ., 2021; Lufti et al. , 2022; Musonda and Okoro, 2022; Battilani et al ., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…These were split into subcategories: status of R & D (individual corporate timelines), innovation, practical experiences, expectations and trends. The collected data was reflected, and the content was analyzed [93] . Connections and similarities between the determined data were analyzed based on an interpretative evaluation following the hermeneutic approach [94][95] .…”
Section: Expert Interviewsmentioning
confidence: 99%